Nanopatterns biofunctionalized with cell adhesion molecule DM-GRASP offered as cell substrate: spacing determines attachment and differentiation of neurons - Jährling, Steffen; Thelen, Karsten; Wolfram, Tobias; Pollerberg, G. Elizabeth (Nano letters, 2009)
The density/spacing of plasma membrane proteins is thought to be crucial for their function; clear-cut experimental evidence, however, is still rare. We examined nanopatterns biofunctionalized with cell adhesion molecule DM-GRASP with respect to their impact on neuron attachment and neurite growth. Data analysis/modeling revealed that these cellular responses improve with increasing DM-GRASP density, with the exception of one spacing which does not allow for the anchorage of a cytoskeletal protein (spectrin) to three DM-GRASP molecules.